Características físico-químicas e sensoriais de embutido fresco de aves de descarte preparado com diferentes antioxidantes naturais - Borba, Hirasilva [UNESP]; Scatolini-Silva, Aline Mary [UNESP]; Giampietro-Ganeco, Aline [UNESP]; Boiago, Marcel. Manente [UNESP]; Souza, Pedro Alves [UNESP] (My University, 2012)
The present study evaluated the effect of the use of natural antioxidants in different spent hens processed meat, the physical-chemical and sensory characteristics of product were analyzed. The experiment was conducted at the Technology Laboratory of Animal Products, Department of Technology - FCAV/Unesp - Campus of Jaboticabal. Forty-five laying hens with approximately 80 weeks of age were used, distributed in a completely randomized experimental design in a 4x4 factorial arrangement, 4 condiment types (control, rosemary, clove and oregano, and the last three natural antioxidants) and 4 storage times (0; 3; 6 and 9 days at 4°C), with sixteen treatments and tree repetitions. It were evaluated the characteristics of humidity, pH, color, cooking loss, shear force, TBARS number and sensory analyze. The averages were obtained by Tukey test 5% of significance. The results showed an interaction between the storage time and condiments types in all analyzed parameters. It was concluded that oregano use decreased the processed meat oxidation, also pleased the judges in sensory analysis. The lowest notes in sensory analysis were obtained with the treatment that contained clove.
Physical-chemical and sensory characteristics of spent hens meat sausage prepared with different naturals antioxidants
Keywords: Poultry; Quality; Storage; Animalia; Origanum; Rosmarinus officinalis; Syzygium aromaticum